2020
DOI: 10.1111/jace.17297
|View full text |Cite
|
Sign up to set email alerts
|

Superheating nature coupled with Mg‐doping effect of high thermal stable NdBa2Cu3O7‐δ film

Abstract: NdBa2Cu3O7‐δ thin film deposited on a MgO substrate has been verified to remain solid above its peritectic melting temperature (Tp). Such a superheating nature is attributed to its low energy surface and epitaxial interface with substrate. Here, combining superheating nature with doping effect, we report a novel structure, Mg‐doped NdBa2Cu3O7‐δ film with YBa2Cu3O7‐δ buffer layer for the first time. Remarkably, this film presents a higher thermal stability level than heretofore possible when acting as a seed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Cai et al 12 reportedly used Nd-123/MgO thin films rather than the Nd-123 bulk crystals as the NdBCO film seeds for the growth of YBCO/Ag grains. Xu et al 13 15,16 reported a novel Mg-doped NdBCO film with a YBCO buffer layer that presented an even higher thermal stability than previously reported, as it endured a temperature of 1128 °C (43 K above its T p ) for 1 h.…”
mentioning
confidence: 92%
“…Cai et al 12 reportedly used Nd-123/MgO thin films rather than the Nd-123 bulk crystals as the NdBCO film seeds for the growth of YBCO/Ag grains. Xu et al 13 15,16 reported a novel Mg-doped NdBCO film with a YBCO buffer layer that presented an even higher thermal stability than previously reported, as it endured a temperature of 1128 °C (43 K above its T p ) for 1 h.…”
mentioning
confidence: 92%